2016
DOI: 10.1093/femsle/fnw127
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation-defective mutants inPseudomonas putida

Abstract: Out of 8000 candidates from a genetic screening for Pseudomonas putida KT2442 mutants showing defects in biofilm formation, 40 independent mutants with diminished levels of biofilm were analyzed. Most of these mutants carried insertions in genes of the lap cluster, whose products are responsible for synthesis, export and degradation of the adhesin LapA. All mutants in this class were strongly defective in biofilm formation. Mutants in the flagellar regulatory genes fleQ and flhF showed similar defects to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
4
24
0
Order By: Relevance
“…However, this phenotype was relatively mild compared to that of the fleQ mutant ( Fig 1A ), as substantial levels of biofilm biomass were achieved. Analysis of other non-motile mutants bearing insertions in the flagellar structural genes flgG , fliF and fliN and fliP yielded similar results [ 40 ]. These results indicate that the loss of flagellar motility does not suffice to explain the severe biofilm formation defect of the fleQ mutant.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…However, this phenotype was relatively mild compared to that of the fleQ mutant ( Fig 1A ), as substantial levels of biofilm biomass were achieved. Analysis of other non-motile mutants bearing insertions in the flagellar structural genes flgG , fliF and fliN and fliP yielded similar results [ 40 ]. These results indicate that the loss of flagellar motility does not suffice to explain the severe biofilm formation defect of the fleQ mutant.…”
Section: Resultsmentioning
confidence: 71%
“…Recently, we undertook the isolation of biofilm-deficient mutants of P putida KT2442 [ 40 ]. Five of our biofilm-deficient mutants were found to bear insertions in fleQ .…”
Section: Introductionmentioning
confidence: 99%
“…All five parallel AgNP-populations acquired a mutation in ftsZ turning the stop codon into a codon for Ser, while in all five Ag + -populations, Arg was substituted with Cys. A similar phenomenon was observed in gacS, which encodes a transmembrane signal sensor protein that is coupled with the response regulator GacA, comprising a two-component system (Heeb and Haas, 2001) that can influence biofilm formation (López-Sánchez et al, 2016). A mutation of uvrY, which is homologous to gacA, occurred in the Ag + -populations and the control populations but was present in only one of the AgNP-populations, implying different regulatory strategies in response to the different Ag species.…”
Section: Discussionmentioning
confidence: 58%
“…However, there are no previous studies reporting S. fuliginis biofilms developed by pure cultures on specific surfaces, being a desirable characteristic that will increment the number of its potential biotechnological applications. Therefore, the ability of the ATCC 27551 strain to form biofilms was evaluated and compared to that of E. coli, P. putida and B. diminuta, better known species for their surface colonization capacity 31,38,39 . Qualitative analyses using crystal violet staining and SEM visualization indicated that all bacterial species can easily colonize the NBARE PCL electrospun microfibers.…”
Section: Discussionmentioning
confidence: 99%